CO(2) Exchange and Dinitrogen Fixation of Subterranean Clover in Response to Light Level - Silsbury, James H. (1981)
Small swards of nodulated subterranean clover plants were grown in pots to a common dry weight under controlled conditions. The rooting medium was a porous calcined clay. All mineral nutrients except nitrogen were supplied daily in solution. Pots then were placed in an assimilation chamber for 3 days for the measurement of net CO(2) exchange at light levels ranging from 0.1 to 2.0 millieinsteins per square meter per second. N(2)-fixation (acetylene reduction) of each pot was measured subsequently. H(2)-evolution and N(2)-fixation were measured for similar treatments in separate experiments using smaller pots. CO(2)-assimilation rate and N(2)-fixation rate responded similarly to increase in light level so that N(2)-fixation was found to be a linear function of both the daily (12-hour) net CO(2)-uptake and of the growth rate (24 hours) of the sward over a wide range. N-concentration of the plants was independent of the light level under which they were grown. The rate of N(2)-fixation per unit weight of nodule varied over a wide range depending on the number of nodules present and on the demand for nitrogen as determined by the growth rate of the sward. It is concluded that the amount of assimilate available to the whole plant is a major factor determining the rate of N(2)-fixation by the whole plant, although it may not be important in determining specific rates of nodule activity. N(2)-fixation per unit weight of nodule therefore is considered to have limited utility for comparative purposes. The relative efficiency of N(2)-fixation was found to be about 0.7 and independent of the level of the incident light after growth at two contrasting light levels, 0.4 and 1.0 millieinsteins per square meter per second.